Synthesis, characterisation and antioxidant properties of ferulate-based protic ionic liquids: Experimental and modelling approaches - Ahmad, N.A. (2019)
Active pharmaceutical ingredients (APIs) in the form of crystalline solid are commonly produced in drug manufacturing industries. However, crystalline solid APIs have a low solubility and the ability to cause polymorphism transformation. In order to overcome these problems, a modification of APIs in the form of protic ionic liquids (PILs) has been proposed. In the present study, a series of five ferulate-based PILs were successfully synthesised and characterised by appropriate spectral analysis. The antioxidant activity of synthesised PILs was determined through the 2,2âdiphenylâ1âpicrylhydrazyl (DPPH) free radical scavenging assays. The spectroscopy analysis confirmed the formation of PILs supported by the Density Function Theory (DFT) calculation. The synthesised ferulate-based PILs exhibited low EC 50 ranging from 12.93 Â± 0.05 to 17.40 Â± 0.04 Î¼M indicating a strong antioxidant activity compared to parent acid (EC 50 of 21.40 Â± 0.05 Î¼M). Prediction of antioxidant activity of the PILs and their ionic interactions at the molecular level were studied by applying DFT calculation at B3-LYP/6-311G*** level and COSMO-RS. Based on the optimised geometry, the ion-pair of PILs formed a strong directional intermolecular hydrogen bond between the âNH group of the cation with the âCOOH group of the anion with interaction energy of â111 to â120 kcal mol â1 . Predicted antioxidant activity indicated that the PILs's cation has a weak interaction with an anion as observed from the Ï-potential analysis. Â© 2019 Elsevier B.V.